Presença de fibromialgia em indivíduos com depressão : uma revisão integrativa - Possamai, Thayla Ribeiro Pegorete (2022)
Depression is a complex condition associated with an affective state of sadness, occurring in response to stressful situations in affective, social and economic life. Its origin is related to left hemisphere hypoactivity, genetic polymorphisms, dysregulation of central and peripheral noradrenergic/serotonergic pathways, dysregulation of pro-inflammatory cytokines, neurosensitization and increase or decrease in serum levels of muscle proteins. It is in this aspect that the predominance of psychological symptoms, which include evidence of cognitive and emotional impairment, can favor the aggravation of physical symptoms and, among them, fibromyalgia is included. A growing body of evidence suggests comorbidity and overlapping symptoms between depression and fibromyalgia and this is also related to lower pain tolerance shown by individuals with depression. The aim of this study was to evaluate the scientific evidence available in the literature on the development of fibromyalgia in individuals with depression. The method of knowledge synthesis adopted was the integrative literature review, guided by the question: “What is the scientific evidence available in the literature on the development of fibromyalgia in individuals with depression?”, which went through six stages for its elaboration. Thus, electronic searches were performed via VHL, PUBMED and Science Direct. The descriptors defined were: Depression, Fibromyalgia, Chronic Pain, Depressive Disorder and Associated Comorbidities. The selection of primary studies was performed by pairs. The studies were entered and stored in the Rayyan program. To collect the data included in the integrative review, a script adapted from the Ursi instrument was prepared, covering aspects such as the identification of the article, type of publication, methodological characteristics of the study and assessment of methodological rigor. The classification system for the quality of evidence selected was the one proposed by Melnyk and Fineout-Overholt. The synthesis and analysis of studies that met the previously established inclusion criteria were performed in a descriptive manner and presented in tables. The sample consists of 06 studies. Regarding the level of evidence, one study presented level of evidence III, and the others, level IV. From the results of this integrative review, it was found that depression and fibromyalgia are conditions that often coexist. However, which disease manifests first and which appears later remains unknown, although some previous longitudinal studies have supported the pain-depression relationship. Even though the relationship between pain perception, processing of pain stimuli and depression is complex and not yet fully understood, it seems reasonable to assume that both depression and pain can arise from the impairment of common neuronal pathways. It is suggested that future longitudinal research be carried out, monitoring patients with depression treated at health services, seeking to identify the development of fibromyalgia in these.